The hero two doors down : based on the true story of friendship between a boy and a baseball legend - Robinson, Sharon, 1950- (Scholastic Press, 2016)
Eight-year-old Steve Satlow is thrilled when Jackie Robinson moves into his Jewish neighborhood in Brooklyn in 1948, although many of his neighbors are not, and when Steve actually meets his hero he is even more excited--and worried that a misunderstanding over a Christmas tree could damage his new friendship.